A development of GPS child tracking wiith GSM module / Nurhasyimah Shahbudin - Shahbudin, Nurhasyimah (Universiti Teknologi MARA, Perlis, 2019)
Child tracking is a system that able to secure and monitor the current location of the children by using parent’s smartphone. The system also includes the movement of the children to and from they want to go. In this project, it designs and develop the GPS child tracking with SMS notification solution to help parents trace their children location by using GPS module and GSM module as the main components. The system will track the location of the children and send the notification to the parent smart phones via SMS. In case of emergency, the system provides a button for the children to send alert message to their parent. So that, the parents will get informed about their children situation and make a move to rescue them. The distance that has been covered by this system also bigger than the other technologies such as RFID and Bluetooth. The RFID and Bluetooth covers the indoors tracking such as in shopping complexes because it covers ten to hundred meters only. Besides that, this system sends the accurate location to the receiver, so that it will become easier for parent to find their children. It also can reduce the parents time and parents can monitor the location of their children even though they in the different location.